(untitled) (Revista Inclusiones, 2019)
Moving academic curriculum towards interdisciplinary curriculum, especially in colleges of humanities, is an objective synchronization of universities with current advances in science and technology interwoven. Attention to the use of interdisciplinary curricula has been placed on the priority of the higher educational system of the country. So, academic interdisciplinary curriculum headlines also require specific indicators to provide interdisciplinary provision. Given the fact that the headlines is considered as the core of the curriculum in university, reviewing the revised headings of the humanities, in light of its designers’ claims on respect for interdisciplinary criteria, needs to be investigated. Of course, before the above-mentioned action, research is needed to develop interdisciplinary indicators for revised headline of the humanities in university. The present study has been designed and implemented to develop the above-mentioned interdisciplinary indicators for headline of the revised humanities in university. For this purpose, first of all, due to the importance of the documents and ratifications of the Supreme Council of the Cultural Revolution and the Upstream Documents of the country as well as other issues discussed in this field, the items related to interdisciplinary indicators was extracted using the method of documentary analysis. Then, from the views of Interdisciplinary specialists, academic curriculum was also used through research interview method and their opinions were gathered. Data from the two sections were coded and categorized and an interdisciplinary indicator framework for headline of the disciplines of the humanities in university was developed using the inference method.